Acute Cerebellitis Associated With Anti-homer 3 Antibodies: A Rare Case Report and Literature Review - Miao, Ailiang; Yu, Chuanyong; Sun, Yulei; Wang, Lingling; Ge, Jianqing; Wang, Xiaoshan (Frontiers in Neurology, 2022)
Acute cerebellitis associated with Homer-3 antibodies is very rare. Here we present a 20-year-old woman who suffered from uncontrollable head shaking quickly from side to side and an unsteady gait for 2 days after the cold. Antibodies were screened by cell-based assays. The indirect immunofluorescence technique results revealed anti-Homer-3 antibody titers of 1:3.2 in the CSF and 1:100 in the serum. The woman was obviously improved after antiviral and immunosuppression (immunoglobin, methylprednisolone and mycophenolate mofetil) treatment. Our report indicated immune-mediated causes should be considered in the acute cerebellitis. Immunotherapy can contribute to the improvement of cerebellar syndrome.